Redox requirements for ubiquitin-like urmylation of Ahp1, a 2-Cys peroxiredoxin from yeast - Brachmann, Cindy (Redox Biol, 2020)
The yeast peroxiredoxin Ahp1, like related anti-oxidant enzymes in other species, undergoes urmylation, a lysine-directed conjugation to ubiquitin-like modifier Urm1. Ahp1 assembles into a homodimer that detoxifies peroxides via forming intersubunit disulfides between peroxidatic and resolving cysteines that are subsequently reduced by the thioredoxin system. Although urmylation coincides with oxidative stress, it is unclear how this modification happens on a molecular level and whether it affects peroxiredoxin activity. Here, we report that thioredoxin mutants decrease Ahp1 urmylation in yeast and each subunit of the oxidized Ahp1 dimer is modified by Urm1 suggesting coupling of urmylation to dimerization. Consistently, Ahp1 mutants unable to form dimers, fail to be urmylated as do mutants that lack the peroxidatic cysteine. Moreover, Ahp1 urmylation involves at least two lysine residues close to the catalytic cysteines and can be prevented in yeast cells exposed to high organic peroxide concentrations. Our results elucidate redox requirements and molecular determinants critical for Ahp1 urmylation, thus providing insights into a potential link between oxidant defense and Urm1 utilization in cells.